Subthalamic nucleus stimulation does not influence basal glucose metabolism or insulin sensitivity in patients with Parkinson's disease - Lammers, Nicolette M.; Sondermeijer, Brigitte M.; Twickler, Th. B. (Marcel); de Bie, Rob M.; Ackermans, Mariëtte T.; Fliers, Eric; Schuurman, P. Richard; La Fleur, Susanne E.; Serlie, Mireille J. (Frontiers in Neuroscience, 2014)
Animal studies have shown that central dopamine signaling influences glucose metabolism. As a first step to show this association in an experimental setting in humans, we studied whether deep brain stimulation (DBS) of the subthalamic nucleus (STN), which modulates the basal ganglia circuitry, alters basal endogenous glucose production (EGP) or insulin sensitivity in patients with Parkinson’s disease. We studied 8 patients with Parkinson’s disease treated with DBS STN, in the basal state and during a hyperinsulinemic euglycemic clamp using a stable glucose isotope, in the stimulated and non-stimulated condition. We measured EGP, hepatic insulin sensitivity, peripheral insulin sensitivity (Rd), resting energy expenditure (REE), glucoregulatory hormones and Parkinson symptoms, using the Unified Parkinson’s Disease Rating Scale (UPDRS). Basal plasma glucose and EGP did not differ between the stimulated and non-stimulated condition. Hepatic insulin sensitivity was similar in both conditions and there were no significant differences in Rd and plasma glucoregulatory hormones between DBS on and DBS off. UPDRS was significantly higher in the non-stimulated condition. DBS of the STN in patients with Parkinson’s disease does not influence basal EGP or insulin sensitivity. These results suggest that acute modulation of the motor basal ganglia circuitry does not affect glucose metabolism in humans.